2001
DOI: 10.1159/000050605
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Serum Sialyl Lewis<sup>a</sup>, Sialyl Lewis<sup>x</sup> and Sialyl Tn Antigens in Blood from the Tumor Drainage Vein of Colorectal Cancer Patients

Abstract: The serum levels of sialyl Lewisa (CA19-9), sialyl Lewisx (SLX), sialyl Tn (STN) and carcinoembryonic antigen (CEA) in peripheral venous blood and tumor drainage venous blood of colorectal cancer patients were examined to determine their value as prognostic factors after surgery. Blood samples were obtained from the peripheral vein and from the tumor drainage vein from 124 colorectal cancer patients during surgical excision of the tumor. The patients were divided into high-antigen and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The presence of carbohydrate receptor sLe X in tumors or serum has been associated well with poor prognosis of various cancers [12,14,16,17] and suggested no other carbohydrate epitope examined to date has equal prognostic value. sLe X expressions in colorectal and non-small cell lung cancer has been correlated with advanced disease, increased distant metastasis and decreased survival [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of carbohydrate receptor sLe X in tumors or serum has been associated well with poor prognosis of various cancers [12,14,16,17] and suggested no other carbohydrate epitope examined to date has equal prognostic value. sLe X expressions in colorectal and non-small cell lung cancer has been correlated with advanced disease, increased distant metastasis and decreased survival [41].…”
Section: Discussionmentioning
confidence: 99%
“…sLe X is frequently expressed on human cancer cells; serve as ligand for E-and P-selectin present on vascular endothelial cells [11,15]. The degree of expression of this ligand at the cancer cells surface is thought to be correlated with the frequency of hematogenous metastasis and prognostic outcome of cancer patients [16][17][18]. It has been shown that expression of sLe X in mucin-type O-glycans is highly associated with lymphatic and venous invasion [19].…”
Section: E-cadherin and Sialyl Lewis-x Oral Carcinogenesismentioning
confidence: 99%
“…5,10,11 The monoclonal antibody GSLA-2 detects the tumor-associated antigen CA19-9, [12][13][14][15] which comprises the sLe a epitope in sera from patients with pancreatic and gastrointestinal cancer. 16,17 An automated cancer diagnostic assay based on GSLA-2 has a proven clinical performance and demonstrates good correlation with the approved CA19-9 assay. 18 The sLe a epitope is characterized by a fucose and a sialic acid residue attached to the type 2 LacNAc core, whereas the sLe x epitope contains the type 1 core structure.…”
Section: Introductionmentioning
confidence: 99%
“…Fujita et al [52] found patients negative preoperatively for CK-19 or CK-20 had significantly fewer recurrences and better 5-year disease free survival. Nakagoe et al [53] found a high sialyl Le (x) antigen or CEA in blood draining the tumour was an independent prognostic indicator of poor survival, and Yamaguchi et al [12] found a similar finding in patients positive for both CEA and CK-20. Other studies show conflicting results, however.…”
Section: Resultsmentioning
confidence: 99%